Rear Optical Reflection and Passivation Using a Nanopatterned Metal/Dielectric Structure in Thin-Film Solar Cells - Lopes, Tomas S. (2019)
Currently, one of the main limitations in ultrathin Cu(In,Ga)Se 2 (CIGS) solar cells are the optical losses, since the absorber layer is thinner than the light optical path. Hence,light management, including rear optical reflection, and light trapping is needed. In this paper, we focus on increasing the rear optical reflection. For this, a novel structure based on having a metal interlayer in between the Mo rear contact and the rear passivation layer is presented. In total, eight different metallic interlayers are compared. For the whole series, the passivation layer is aluminum oxide (Al 2 O 3 ). The interlayers are used to enhance the reflectivity of the rear contact and thereby increasing the amount of light reflected back into the absorber. In order to understand the effects of the interlayer in the solar cell performance both from optical and/or electrical point of view, optical simulations were performed together with fabrication and electrical measurements. Optical simulations results are compared with current density-voltage (J-V) behavior and external quantum efficiency measurements. A detailed comparison between all the interlayers is done, in order to identify the material with the greatest potential to be used as a rear reflective layer for ultrathin CIGS solar cells and to establish fabrication challenges. The Ti-W alloy is a promising a rear reflective layer since it provides solar cells with light to power conversion efficiency values of 9.9%, which is 2.2% (abs) higher than the passivated ultrathin sample and 3.7% (abs) higher than the unpassivated ultrathin reference sample.